Experimental results of electric vehicles effects on low voltage grids. (10th May 2020) - Zou, Yuwei; Zhao, Junfeng; Gao, Xiangming; Chen, Yongchao; Tohidi, Akbar
Abstract: Today, the second largest source of greenhouse gases production is due to transportation. A quarter of the greenhouse gas emissions which are generated in the European Union (EU) is due to transportation. One of the main greenhouse gas emissions is CO2 gas and about 15% of greenhouse gas emissions, which is CO2, are produced through light vehicles such as pickups and cars. On the other hand, due to increased utilization of electric vehicles, the power grid structure needs to be developed and improved. Because of the vehicles effect on the low voltage network, distribution service operators (DSOs) will prepare the failed for the mentioned effects. In this paper, the impact of charging electric vehicles on low voltage networks structure and technology of electric vehicles have been investigated. A novel upper and lower based voltage controller is introduced as distributed agent-based model to control the voltage stability in test smart grid. In the proposed method, based on rule defining for distributed agent, the electric vehicle (EV) charging will cooperate with smart grid and its charging time will be moved from peak time to other times. By this action of agents, the smart grid load and the stability of voltage can be managed beside the economic benefits consideration. In order to evaluate the performance of the proposed method and the effect of electric vehicles, this method has been implemented on a low voltage network of a restricted district of Budapest based on DIGSILENT. According to obtained results, it could be considered that the maximum transformer loading with EV is about 41% and 36.6% without EV. Furthermore, transformer loading is about 14.761% for common arrival simulations to 10.072% without EVs. So, the proposed model can be effective in low voltage grids of transmission by preventing the pollution. The aforementioned district is characterized by predominantly low to medium density residential dwellings, where private off-street parking is available to facilitate the charging of electric cars from a conventional single-phase household power outlet. Highlights: Implementation of EV charging scenarios in simulations and data collected during time sweep. Application of stochastic analysis for the load profiles in 24-h period. Presenting the current state of EV and charging effects on low voltage grids. Investigating the effects of charging both spatially and temporally, using time sweep analysis. Analysis of electricity grid infrastructure's requirements for reinforcement and upgrading.